Final Fantasy VII Intergrade Chapter 17: Deliverance from Chaos’ Maxim Violations - Abdussalam Jabaruddin Yamjirin (Translation and Linguistics (Transling), 2025)
Video games have evolved into a sophisticated narrative medium, seamlessly blending interactivity with complex storytelling. Unlike traditional media, games offer players an immersive role, allowing them to experience narratives dynamically rather than passively consuming them. Final Fantasy VII Remake Intergrade exemplifies this evolution, using character dialogue to deepen engagement and emotional investment. However, within its intricate narrative, conversational maxims, established by Grice’s Cooperative Principle, are frequently violated, creating layers of meaning that enhance storytelling. This study explores maxim violations in Final Fantasy VII Remake Intergrade: Chapter 17 - Deliverance from Chaos, analyzing how these pragmatic deviations shape character development, dramatic tension, and player interpretation. Through qualitative analysis, four primary categories of maxim violations (Quantity, Quality, Relevance, and Manner) are identified, each serving a distinct function in the game’s narrative. Findings suggest that these violations are not mere linguistic anomalies but deliberate storytelling devices that reinforce themes of mystery, deception, and emotional depth. By bridging pragmatics and interactive media, this research contributes to the understanding of how digital narratives employ language to craft compelling experiences, opening avenues for further exploration in game studies and linguistic pragmatics.